2022
DOI: 10.1080/13576275.2022.2136515
|View full text |Cite
|
Sign up to set email alerts
|

Talking about death and dying: Findings from deliberative discussion groups with members of the public

Abstract: Talking about death and dying is promoted in UK health policy and practice, from a perception that to do so encourages people to plan for their end of life and so increase their likelihood of experiencing a good death. This encouragement occurs alongside a belief that members of the public are reluctant to talk about death, although surveys suggest this is not the case. This paper describes findings from a research study in which people participated in deliberative discussion groups during which they talked ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The idea that the public has an aversion to talking about death and dying, and that death remains a social ‘taboo’ has been vigorously promoted by a diverse range of social movements and interest groups since the 1960s. Nevertheless, then as now, there is little evidence to support these claims as attitudes to death and dying have not been extensively researched ( Wilson et al, 2022 ). What’s more, there were little research on the relationships between talking about death and subjective well-being among the middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that the public has an aversion to talking about death and dying, and that death remains a social ‘taboo’ has been vigorously promoted by a diverse range of social movements and interest groups since the 1960s. Nevertheless, then as now, there is little evidence to support these claims as attitudes to death and dying have not been extensively researched ( Wilson et al, 2022 ). What’s more, there were little research on the relationships between talking about death and subjective well-being among the middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nursing staff discussing the topic of death with the middle-aged and older adults and their families can provide them with spiritual comfort and psychological counseling, so that the middle-aged and older adults can correctly understand death and free themselves from fear (Chua and Shorey, 2021). Overall, prior findings suggest that the "taboo" against death talk may be more perceived than real (Wilson et al, 2022). We will review the literature on talking about death from five dimensions: the way of talking about death, the attitude toward talking about death, the objects of talking about death with, the frequency of talking about death and the content of the death talk.…”
Section: Talking About Deathmentioning
confidence: 98%
See 1 more Smart Citation
“…Participants suggested peer-mentors could provide both "practical" and "emotional" support to families. Tis phrasing has also been highlighted in previous research [13] which explored public attitudes to talking about death and dying and therefore may shed light on the ways the public understand their support needs around preparing for discussions and decisions about deterioration and the end-of-life. Although existing research has suggested that peer-support can be benefcial for family members who support a person living at home [26,[31][32][33], the fndings of the current study suggest that peer-mentors could also be benefcial to family members who support a relative living in a care home.…”
Section: Comparison With Existingmentioning
confidence: 99%
“…Families may not have a good understanding of their relative's wishes and preferences with regards to end-of-life care and treatment [10], which can lead to feelings of uncertainty [11] and experiences of stress, anger, regret, and guilt [12,13]. Family members may not know what to expect as their relative's condition deteriorates and, although willing, may be unprepared to be involved in decisions about end-of-life care.…”
Section: Introductionmentioning
confidence: 99%